Anchor Stress and Deformation of the Bolted Joint under Shearing - Hang Lin; Youyan Zhu; Jianyu Yang; Zhijie Wen (Advances in Civil Engineering)
Bolts are widely used in rock mass engineering, wherein the bolt support improves the safety and stability of the rock mass. To reveal the mechanical behavior of the bolt and failure mechanism of the bolted joint in the shearing process, a direct shear test was conducted by changing the state of grouting, number of bolt, and inclination angle of the bolt. The change in the axial force of the anchor in the shearing process was evaluated by conducting a strain gauge test, and the mechanical behavior of the bolt under the external force was studied. The results showed that under the same normal stress, the yield displacement of the bolt decreased and the stiffness of the joint gradually increased with increased number of bolts. At the same number of bolts, their yield displacement increased with increased normal stress. Analysis further revealed that grouting on the joint improved the force condition of the bolt, increased the yield displacement of the bolt, and coordinated the deformation of the grouting body and bolt, thereby improving the shear strength of the joint. Lastly, when the anchor angles differed, the axial pulling resistance of the anchor changed, and the yield displacement of the anchor with 45° inclination was <90°. The yield displacement of the bolt showed that the supporting effect of the bolt with a 45° inclination was better than that of the bolt with a 90° inclination.